Նոր աշխարհակարգի մարտահրավերները փոքր պետությունների դիվանագիտությանը - Նավասարդյան, Արման (YSU Journal of International Affairs, 2015)
In this article, the author refers to two antagonistic blocs of political and diplomatic struggle in the process of the creation of a new world order afterthe collapse of the Soviet Union and the Cold War. In this context, the author tries to analyze an important question which was missed from the politicians’ attention: it is the position of small and especially newly independent countries to the abovementioned superpower conflict and the century challenges. It is mentioned that the erosion of the empires brings with it latent ethnic animosity of the liberated sovereign small countries causing clashes and military operations in different regions. Some authors areinterested in the possible elimination of borders of internal and foreign policy of countries and the opponents’ opinions of that bill. Stopping on the aspiration of seeing the world unipolar by the USA and multipolar by Russia, China and a number of countries, the author believes, that the establishment of a multi-polar world will promote the national interests of the Armenian Republic.
Keywords: a new world order, “torn fragments” of empires, erosion of system of Vestfal and Yalta-Potsdam, Elimination of internal and external political boundaries, bipolar world order, national interests and national security